DOES SUSTAINABILITY MATTER IN MERGERS AND ACQUISITIONS? THE CASE OF THE SERBIAN FOOD INDUSTRY - Ksenija Dencic-Mihajlov (Ekonomika Poljoprivrede (1979), 2020)
This paper investigated key areas in which environmental, social and governance issues may be important in M&A transactions, with a particular emphasis on the Serbian food industry. The analysis was conducted using a sample of 11 realized M&As in the Republic of Serbia with the food producers as target companies and is based on the data acquired from the targets` annual reports and web sites. The analysed transactions, that have been randomly elected, belong to different legal types of M&A: acquisition of asset, acquisition of shares, tender offer and merger/consolidation. Following the classification of sustainability issues, two types of M&A in the Serbian food industry have been distinguished: one enables the acquirer to build the presence in the key segments with sustainability products in line with modern health trends, while the other helps the buyer to improve synergies and consolidate leadership position by acquiring target with a recognized sustainability profile and credibility.